A case of gambling addiction applying to the emergency department with a suicide attempt - Geniş, Bahadır; Aksu, Hakan (Journal of Dependence, 2020)
Gambling addiction (GA) is a disorder characterized by repetitive gaming that persists despite negative consequences and leads to a decrease in functionality.Suicidal thoughts and suicide attempts are higher in people with GA than in society. In this study, a case of GA applying with suicide attempt is presented and treatment modalities are discussed.A 29-year-old male patient, married, high school graduate and working as a worker, was brought to the emergency room after a suicide attempt. He had been experiencing symptoms of depression for the past three months due to increased debt.After his family learned about his gambling debt, the patient attempted suicide by drinking medicine.In her mental state examination, her memory and attention decreased, her speech was slow, her mood was depressed. The patient had no symptoms of mania.According to DSM-5 diagnostic classification, it was determined that there was a diagnosis of “Gambling Addiction”. In addition to this diagnosis, he had depression. For his depression, sertraline 50 mg/day and risperidone 1 mg/day were started.In addition, cognitive and behavioral therapy was initiated for GA. The patient, who was on follow-up for about five months, stated that he did not gamble especially after the start of psychotherapy.His depressive symptoms improved significantly after the first month. Financial problems, problematic family relationships and added psychiatric diseases caused by the GA increase the risk of suicide attempt.Applications for GA treatment are very few. Psychiatric comorbidity and suicidal ideation should be questioned in the applicants.